ACCURACY OF A MULTIPLEX PCR PROTOCOL FOR Staphylococcus aureus, Streptococcus agalactiae AND Escherichia coli DETECTION IN BULK TANKS - Troncarelli, Marcella Zampoli; Langoni, Helio; Pereira, Virginia Bodelão Richini-; Marson, Pâmela M.; Silva, Rodrigo Costa Da (Veterinária e Zootecnia, 2022)
The objective of the present study was to evaluate the accuracy of a multiplex PCR (mPCR) protocol for Staphylococcus aureus, Streptococcus agalactiae and Escherichia coli detection in bovine milk samples collected from bulk tanks. Twenty dairy farms in mid-west of Sao Paulo State, Brazil were enrolled. Milk samples collected from each bulk tank were evaluated by mPCR and microbiological culture (gold standard test). S. aureus, S. agalactiae and E. coli were isolated by culture in 30%, 10% and 40% respectively, and detected by mPCR in 0%, 10% and 35% bulk tank milk samples respectively. mPCR has demonstrated 93.2% specificity and 37.5% sensitivity values, with 78.3% accuracy. It was possible to conclude that this mPCR protocol was efficient for S. agalactiae and E. coli detection in the evaluated bulk tank milk samples, but failed to detect S. aureus. Despite the high specificity values obtained by mPCR, the sensitivity levels were low, indicating that this molecular method should only be recommended as a complementary diagnosis test for milk quality monitoring in bulk tanks.